2004
DOI: 10.1557/jmr.2004.0229
|View full text |Cite
|
Sign up to set email alerts
|

New lead-free relaxors based on the K0.5Na0.5NbO3–SrTiO3 solid solution

Abstract: New lead-free relaxors have been produced from the K0.5Na0.5NbO3–SrTiO3 (KNN-STO) system. The solid solubility within the studied range of compositions (1 - x) K0.5Na0.5NbO3–xSrTiO3 was observed for x up to 0.33. A pseudo-cubic perovskite structure was determined for x = 0.15 to 0.25. The high density and the uniform distribution of fine grains and pores were confirmed by the translucency of these ceramics. The 0.85KNN-0.15STO composition reaches the dielectric permittivity of above 3000 at room temperature. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(85 citation statements)
references
References 16 publications
5
75
0
1
Order By: Relevance
“…By incorporating with different end members, such as LiNbO 3 and SrTiO 3 , the materials show good sinterability and piezoelectric properties. [8][9][10] Lang et al 11 reported the piezoelectric and pyroelectric properties of the KNN-based ceramic. The d 33 and p coefficient were found to be 289 pC / N and 160 C / m 2 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating with different end members, such as LiNbO 3 and SrTiO 3 , the materials show good sinterability and piezoelectric properties. [8][9][10] Lang et al 11 reported the piezoelectric and pyroelectric properties of the KNN-based ceramic. The d 33 and p coefficient were found to be 289 pC / N and 160 C / m 2 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…4) From the industrial point of view, conventional sintering is required for mass production. Recently, many researchers have investigated the effects of small amounts of dopants in NKN ceramics such as LiNbO3, 5) LiTaO3, 6) BaTiO3, 7) SrTiO3, 8) and LiSbO3,9) to improve the ceramics' piezoelectric properties. Among these dopants, (Na,K,Li)(Nb,Ta)O3 is a very promising system with improved properties.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Although no electrostrictive effect has been reported in KNN 20,21 Counterparts of the above mentioned BNT-, BT-, and KNN-based electrostrictors with pseudocubic/cubic structure can be designed in the center pseudocubic/cubic area of the phase diagram shown in Fig. 1.…”
mentioning
confidence: 99%